Duvā Nāmmasetāeśane, tarajumo tathā sareha sāthe - Kaṭelī, Khuraśedajī Minocerajī (Rāhanumāe Mājadīaśanā Sabhānī Kārobāra Maṇḍalī, 1872)
Essay on selections from Dinkard, Zoroastrian sacred book with critical interpretation.